Role of Codeswitching in the Talk of Primary School Mathematics and Science Teachers - Zakaria, Razimi (2009)
The of teaching Mathematics and Science in English or Pengajaran dan Pembelajaran Matematik dan Sains dalam Bahasa Inggeris (PPSMI) at the primary school levels in Malaysia was implemented in 2003. However, the lack of adequate proficiency in the language among the teachers of these subject areas became a central issue in the implementation. Questions were raised on how teachers and students coped with teaching and learning the subjects in English, strategies employed by Mathematics and Science teachers to deliver the lessons in English and the role of first language in the teaching of Mathematics and Science in Malaysian classrooms. The purpose of the study was to explore the role of codeswitching in the talk of Mathematics and Science primary school teachers. This research was undertaken to investigate the categories of teacher talk where codeswitching occurred, the functions of codeswitching in these categories and teachers’ perceptions on the use of their first language when teaching Mathematics and Science. Qualitative inquiry was selected as the methodology for this study as it was deemed the most appropriate for exploring the role of codeswitching in the talk of Mathematics and Science primary school teachers. Data were generated and gathered through interviews with five teachers from three government schools in Kelantan. The participants were selected based on purposive sampling. The data collection methods to achieve the purpose of this study were in-depth interview and non-participant observation. The classroom observations and interviews were video-taped using a camera recorder, transcribed verbatim and analysed manually. Emerging themes from the classroom data were used to develop the Table of Codeswitching Categories to facilitate analysis of codeswitching in teacher talk. Teacher utterances were transcribed, coded and tally counts were made to generate frequency distributions of talk types. The distributions were later compared with the frequencies of codeswitching that occurred in the respective categories. The quantitative analyses demonstrated the categories of teacher talk in which they were inclined to codeswitch when teaching Mathematics or Science. Qualitative analyses were obtained from forms of descriptive narrations to illustrate the functions of codeswitching in the talk of PPSMI teachers. Data from teacher interviews were transcribed and the themes that developed during the analysis were highlighted. Input from the interviews provided information on the teachers’ background and their choice to codeswitch when teaching Mathematics or Science to their students. The findings revealed that teacher talk dominated the interaction climate in the classrooms and codeswitching was a coping strategy in the Mathematics and Science teacher’s talk to deliver the subject content. It was found that the teachers frequently codeswitched to their first language when giving explanations, mainly for the purpose of explaining meanings of English words or phrases and clarifying lesson content. Lesson difficulty and types of classroom activities were found to influence the amount of codeswitching in teacher talk. Less codeswitching occurred in the classrooms if the lesson content was simple and learning comprised more repetition activities. Questioning was done mainly for the purpose of asking for translation of English words or phrases. Analyses of interview data revealed that students’ understanding of the lesson content was the main concern of Mathematics and Science teachers. Ensuring students’ understanding of the meaning of English words, phrases and concepts was the main source of teachers’ decision to codeswitch during the lessons. In summary, the findings of this research showed that the use of codeswitching in the talk of the teachers was primarily to facilitate and ensure understanding of the lesson content among the students. The findings of this research give insights to practitioners in ESL about the roles of codeswitching in the content-based classrooms as well as to raise their awareness of the benefits and drawbacks of codeswitching in classrooms.